EFFECTIVENESS OF GROUP COUNSELING SERVICES TO IMPROVE EMOTIONAL INTELLIGENCE - Prof. Mudjiran (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The research is based on the problems low emotional intelligence of students. The purpose of research is to gain an overview of the increase emotional intelligence of students through the Guidance Services Group at SMA Negeri 10 Padang. True experimental research design with pretest-posttest form Control Group Design. With a sample of experimental class is class XI IPA U-1 class of 10 students and control is of class XI IPA U-2 as many as 10 students so as the total sample of 20 students. In experiments conducted classes meeting three times. While the control class three meetings. The data were analyzed using the Wilcoxon Signed Ranks Test and Kolmogorov Smirnov z with SPSS version 20.00. From the results of the implementation is done, there was a significant increase is mainly posttest experimental class. The findings in the experimental group and the control group there were significant increases between the posttest and posttest control group experimental class. On average variable emotional intelligence of 120.50 (posttest experiment) while the control group 107.00 (posttest control) this looks very significant difference. The conclusion of this study indicate that the effectiveness of group counseling services can improve emotional intelligence of students in grade XI SMA Negeri 10 Padang